Facetten der japanischen Populär- und Medienkultur 3 (Harrassowitz Verlag, 2016)
Since the triumph of the internet and the opening up of new possibilities for the dissemination of cultural knowledge, fan activities have reached unimagined dimensions and are seen as "participatory media cultures" mostly positively due to their transcultural connecting potential. The now third facet volume on popular and media culture in Japan is dedicated to in seven contributions, the interactions between the media industry and cultural production in the context of fandom.Three contributions analyze transmedial narrative concepts between manga, video game and merchandising.The focus is on the "light novel", Japanese novels in manga style, video games that convey historical knowledge and the phenomenon of the ubiquitous "imperfect" regional advertising mascots (yurukyara). Two other articles deal with the fan medium of dōjin shi, in which characters from existing manga or anime series are reused. On the one hand, reasons for this are shown gt that these fan works are tolerated even in the case of clear copyright violations, on the other hand the dōjinshi are characterized as a "hybrid economy" and contrasted with western fan fiction on the Internet, which is referred to as the "gift economy". Another contribution analyzes images of women and femininity in the Takarazuka revue founded in 1914 and for the first time focuses on the performers of female roles (musumeyaku). Finally, a contribution to television culture examines the established format of the Japanese series Mare (2015) with a special focus on its importance for the revitalization of rural regions and the construction of national identity in the digital age.